Genome-wide identification of the superoxide dismutase gene family in Lycium barbarum and their expression profiles under abiotic stress and phytohormone treatment - Xiaoyu Cao; Xiaorong Bai; Yingwu Li; Xuedong Hui; Jinfeng Niu; Xiaojie Liang; Yue Yin; Wei An (Frontiers in Plant Science, 2026)
Background Superoxide dismutases (SODs) are crucial metalloenzymes that constitute the first line of defense against reactive oxygen species in plants under abiotic stress. Wolfberry ( Lycium barbarum ) is an economically important medicinal plant with notable stress tolerance, however, a comprehensive genome-wide analysis of its SOD gene family has not yet been performed. Results We identified ten wolfberry SOD genes ( LbaSODs ) and classified them into three subfamilies: iron-SODs (Fe-SODs), manganese-SODs (Mn-SODs), and copper/zinc-SODs (Cu/Zn-SODs). Members within each subfamily shared conserved gene structures and motifs. Segmental duplication was the primary driver of LbaSOD expansion, with three paralogous pairs identified. Analysis of cis -regulatory elements in the promoter region revealed a predominance of stress- and hormone-responsive cis -elements, particularly ABA-responsive elements (ABREs) (22 copies) and LTR (17 copies) motifs. Tissue-specific expression profiling revealed that LbaSOD2 and LbaSOD5 expression peaked during early fruit development, whereas LbaSOD6 , LbaSOD9 , and LbaSOD10 were progressively upregulated through fruit maturation. Under abiotic conditions, Fe-SOD members were markedly suppressed during prolonged drought, whereas LbaSOD9 and LbaSOD10 were rapidly induced in response to salt stress. Among the phytohormone treatments, methyl jasmonate (MeJA) elicited the most pronounced response, with LbaSOD5 expression increasing by approximately 60-fold after 24 hours. Notably, abscisic acid (ABA) triggered an exceptionally strong transcriptional induction of LbaSOD5 (2.5 × 10 5 -fold), LbaSOD10 (6 × 10 5 -fold), and LbaSOD6 (70-fold). In addition, LbaSOD3 and LbaSOD7 transcripts were undetectable in any of the tested conditions. Conclusions This study provides the first comprehensive characterization of the LbaSOD gene family and elucidates its hormone- and stress-responsive regulatory landscape, providing a valuable foundation for future functional investigations of LbaSOD genes in abiotic stress adaptation. The extraordinarily strong ABA-mediated induction of specific LbaSOD members, together with their tissue- and stress-specific expression patterns, highlights their potential as targets for genetic improvement of stress tolerance in wolfberry.